UPAYA DINAS PENDIDIKAN KOTA PEKANBARU MENGANTISIPASI ANAK PUTUS SEKOLAH DI KOTA PEKANBARU TAHUN 2021 - Nuriaini, Yusrah Febri; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Education is an important aspect in the development of a nation. Almost every country prioritizes educational development among other developments. Education is a right for every Indonesian citizen and an obligation for the state. Even though it is clearly stated that the minimum education that every citizen must complete is twelve years, in reality there are still children in Pekanbaru City who have dropped out of school. And of the 15 sub-districts in Pekanbaru City, the number of children dropping out of school is mostly found in Tenayan Raya District. The background to this research is that even though the Pekanbaru City Government has issued a policy to deal with out-of-school children, there are still out-of-school children in Pekanbaru City. The research method used in this research is a qualitative method with descriptive research type. The data collection techniques used were interviews and documentation. The data analysis technique used in this research has stages such as data collection, data reduction, data presentation and drawing conclusions. Based on the results of the research, it was concluded that there are no programs and fields that specifically deal with out-of-school children. The efforts made by the Education Department are by providing financial assistance sourced from zakat from employees within the Education Department and outreach to increase parents' understanding of the importance of education. However, these efforts have not yet run optimally because it can be seen that there are still parents who do not know about this. Keywords: Education, Dropout, Effor